MODELLING OF THE ALGORITHM FOR DEFINITION OF THE TOOTH CROWN'S COLOR SHADE BASED ON STM32F4XX SERIES MICROCONTROLLERS - P. A. Burdavitsyn; V. V. Shatalova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Here's a variant of implementation of the algorithm for definition of the tooth crown's color shade with adaptation’s function to external conditions based on stm32f4xx series microcontrollers and color sensor module TCS3200.